Analysis of Learning Interest in Religious Studies - Muthiah Muthiah; Wilson Wilson; Dafetta Fitrilinda; Asmiah Asmiah (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
Interest is an important foundation for a person to do activities well, but after observation, the author found several things that are considered to be problems in the interest of students in the teaching and learning process, including: the lack of enthusiasm of students in participating in memorization lessons of the Surah-surah of the Qur'an in Maktab Darunna'im, which can be seen from the number of students who are rarely present at every meeting,  In addition, it can also be seen from the lack of responsibility of students in each task given, such as memorization and written assignments, therefore this study aims to analyze the extent of the interest in learning maktab darunna'im students towards the learning provided Sampling techniques using the Simple Random Sampling method, The data collection method in this study is by observation and questionnaire. Research instruments.through several stages, namely: 1) Examine all theory which is related to variables which will be studied, 2) Compile indicators of each variable, 3) Compile a grid of instruments, 4) Compile statement items and establish scale measurements, 5) Test Instruments, 6) Analyze the question items by testing the validity and reliability of each item of the statement. Based on the analysis of the interest in learning students of Maktab Darunna'im, Pekanbaru City sail district is quite high, obtaining a Mean value of 3.43 and a Standard Deviation of 0.36. With the acquisition of the indicator mean as follows: 1) Feeling of Pleasure obtaining a Mean value of 3.43 and Standard Deviation of 0.42, with a moderate interpretation, 2) Interest in learning to obtain a Mean value of 3.44 and a Standard Deviation of 0.36 with a moderate interpretation, 3) Showing attention when learning to obtain a Mean value of 3.42 and a Standard Deviation of 0.37 with a moderate interpretation, 4) Involvement while studying obtained a Mean value of 3.39 and a Standard Deviation of 0.44 with a moderate interpretation. Based on the formulation of the problem, hypothesis and research results, it can be concluded that there is a positive and significant influence on the research. Based on the data that has been collected and the tests that have been carried out, it can be concluded that the level of Interest in Learning Santri Maktab Darunna'im, Sail District, Pekanbaru City, is already in a fairly high category.